Cancer Screening: Construction of a Plasmonic Chip for Metabolic Analysis in Cervical Cancer Screening and Evaluation (Small Methods 4/2020). Issue 4 (14th April 2020) - Shu, Weikang; Wang, You; Liu, Chao; Li, Rongxin; Pei, Congcong; Lou, Weihua; Lin, Sihan; Di, Wen; Wan, Jingjing
Abstract : In article number 1900469 by Wen Di, Jingjing Wan, and co‐workers, gold/dopamine‐bubble plasmonic chips are assembled to realize fast, sensitive and selective metabolic fingerprints in human serum without any pretreatment. On‐chip serum fingerprints further allows for the discrimination of patients with cervical cancer from control subjects, as well as the therapeutic evaluation for potential clinical monitoring.